PENYELESAIAN SENGKETA ADMINISTRASI TERHADAP HASIL SELEKSI CALON ANGGOTA KPU/BAWASLU DI PROVINSI DAN KABUPATEN/KOTA - Mawardi, Irvan (Bawaslu Provinsi Jawa Barat, 2021)
The General Election Commission (KPU) and the Election Supervisory Agency (Bawaslu) will select election organizers gradually in advance of the 2024 General Election and Regional Election. The time period will end in 2022 or 2023. Such circumstances will have an impact on election preparations and regional head elections. Disputes over the selection stages and results at the State Administrative Court are one of the potentials that can disrupt the selection process for organizers and affect the stages of the general election and local elections. A lawsuit that appears in the middle of the selection stage has the potential to create uncertainty about the schedule for the next selection stage. This is because the Defendant in the Administrative Court is the Selection Team, not the Chairperson of the General Election Comission (KPU)/the General Supervisory Agency (Bawaslu). Furthermore, the dispute resolution process in the Administrative Court takes a long time. The purpose of this study is to examine the administrative dispute resolution arrangement in the selection of election organizers by looking at two things: (1) the legal position of the provincial/district election organizers selection team in dispute in the Administrative Court, and (2) the effectiveness and efficiency of the State Administrative Court's adjudication of the selection results.